2018
DOI: 10.22256/pubvet.v12n3a42.1-9
|View full text |Cite
|
Sign up to set email alerts
|

Check List of the parasites of the ocean sunfish (Mola mola: Molidae) fish in the world

Abstract: RESUMO. Devido à escassez de trabalhos relacionados ao parasitismo no mundo, sendo assim, percebe-se a importância de realizar uma revisão bibliográfica em artigos científicos, dissertações e teses em bancos de dados e periódicos de fácil acesso para os estudantes e pesquisadores acerca das ocorrências de parasitas em M. mola entre os anos de 1904 -2017. A espécie de peixe conhecida popularmente como peixe lua (Mola mola: Molidae) são encontrados em todos os oceanos do mundo. O parasitismo pode ser uma das pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Regarding to the other helminths identified in the present study, the cestodes H. trichiuri (Sphyriocephalidae) and A. microcephalus (Triaenophoridae) parasitize as adults the intestine of pelagic sharks and Molidae fishes respectively (5,6,26,41,42,47,48). It is believed that copepods can serve as intermediate hosts for both cestode species (48,54).…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…Regarding to the other helminths identified in the present study, the cestodes H. trichiuri (Sphyriocephalidae) and A. microcephalus (Triaenophoridae) parasitize as adults the intestine of pelagic sharks and Molidae fishes respectively (5,6,26,41,42,47,48). It is believed that copepods can serve as intermediate hosts for both cestode species (48,54).…”
Section: Discussionmentioning
confidence: 76%
“…Small crustaceans (Euphausiidae), fishes, squids, and other invertebrates serve as first and second intermediate or paratenic hosts (43,44). Anisakis larvae have been previously reported in Mola species from Spain, New Zealand, and Chile (5,6,42), although no molecular analyses were performed to identify those larvae to species level. Anisakis simplex (s.s.) is known from the Atlantic and Pacific Oceans, and has its southern limit of distribution in the North-Eastern Atlantic waters along the Spanish-Portuguese Atlantic coast, being never recorded in the Mediterranean Sea except from the Alboran Sea, a transitional zone between Atlantic and Mediterranean [see (43)], and in pelagic fishes like the Atlantic mackerel Scomber scombrus Linnaeus, 1758 and the Atlantic bluefin tuna Thunnus thynnus Linnaeus, 1758 in the Eastern Mediterranean (45,46); however, it has been suggested that the latter findings were related to the large migratory routes of those intermediate/paratenic fish hosts (45,46).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations